2015
DOI: 10.1007/s00449-015-1433-4
|View full text |Cite
|
Sign up to set email alerts
|

Flow-injection chemiluminescence method for the determination of moxifloxacin in pharmaceutical tablets and human urine using silver nanoparticles sensitized calcein–KMnO4 system

Abstract: Silver nanoparticles have been synthesized and were utilized for the enhanced luminometric estimation of moxifloxacin antibiotic. During the experimental procedure, it was clearly found that the addition of silver nanoparticles intensifies the weak chemiluminescence signal intensity of calcein-KMnO4 system by several folds. It was also obvious that the intensity enhancement was linearly proportional to the moxifloxacin concentration and this phenomenon was further utilized for the quantitative determination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The results showed CL intensity was linear over the concentration range of 5.6×10 -9 -2.2×10 -6 M, which is more widely linear and sensitive than previously reported results [41][42][43] , where the linear range was 1.0×10 -7 to 1.0×10 -4 M. The limit of detection (LOD) as defined by IUPAC, C lod = 3×Sb/m, where Sb is the standard deviation of the blank signals and m is the slope of the calibration graph) was found to be 1.5×10 -9 M, while in the previous report it was 5.6×10 -9 M [42,43] . The correlation coefficient for the calibration curve was 0.9998.…”
Section: +mentioning
confidence: 54%
See 1 more Smart Citation
“…The results showed CL intensity was linear over the concentration range of 5.6×10 -9 -2.2×10 -6 M, which is more widely linear and sensitive than previously reported results [41][42][43] , where the linear range was 1.0×10 -7 to 1.0×10 -4 M. The limit of detection (LOD) as defined by IUPAC, C lod = 3×Sb/m, where Sb is the standard deviation of the blank signals and m is the slope of the calibration graph) was found to be 1.5×10 -9 M, while in the previous report it was 5.6×10 -9 M [42,43] . The correlation coefficient for the calibration curve was 0.9998.…”
Section: +mentioning
confidence: 54%
“…Only a few researchers reported that their method was less tedious as compared to the other. Different pharmaceuticals have been determined using the above mentioned system, our previous method was based on calcein-KMnO 4 system with a linear range of 6.0×10 -8 M to 2.5×10 -6 M with a LOD of 5.6×10 -9 M [43] . Suh et al reported MF determination using microfluidic chip assisted luminol-ferricyanide system [44] .…”
Section: +mentioning
confidence: 99%
“…The existing technologies/methods for estimation of DUV are mostly chromatographic including UHPLC-MS/MS [10], HPLC-UV [11,12], HPLC-FD [13], and spectrophotometric assays [14]. The available techniques for estimation of MOX include HPLC [15][16][17][18][19], LC-MS [20,21], mass spectrometry [22], electrochemical methods [23], micellar electrokinetic capillary chromatography [24], spectrophotometry [18,[25][26][27][28][29][30][31], spectrofluorimetry [32][33][34] and chemiluminescence-based methods [35]. All these methods were developed for estimation of DUV and MOX individually; however, there is no any method for their simultaneous estimation.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decade, analytical applications of NPs have widely been explored in CL methods. 14,24,[31][32][33][34][35][36][37][38][39][40][41][42][43] It has been reported that NPs can enhance luminol-oxidant CL signals and analytes could enhance or inhibit the CL signals from luminol-oxidant-NPs system. Cysteine (a -SH containing amino acid) have been determined using some of these methods.…”
Section: Introductionmentioning
confidence: 99%